Pengaruh Capital Intensity dan Sales Growth terhadap Agresivitas Pajak dengan Profitabilitas sebagai Moderasi: Studi pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia tahun 2021-2024 - Putu Nadya Somatariska; I.G.A Desy Arlita; Putu Sri Arta Jaya Kusuma; I Gusti Agung Ayu Pramita Indraswari (As-Syirkah: Islamic Economic & Financial Journal, 2025)
Tax aggressiveness refers to corporate actions aimed at engineering earnings and reducing tax burdens through aggressive tax avoidance practices, either legally or illegally. This study examines the effect of capital intensity and sales growth on tax aggressiveness with profitability as a moderating variable in energy sector companies listed on the Indonesia Stock Exchange during 2021-2024. This research employs a quantitative method using secondary data in the form of corporate financial statements. The sampling technique utilized is purposive sampling, resulting in a sample of 29 companies with 116 observations. The data analysis technique employed is Moderated Regression Analysis (MRA). Based on the analysis conducted, the results indicate that capital intensity and sales growth have a significant negative effect on tax aggressiveness. Profitability strengthens the effect of capital intensity and sales growth on tax aggressiveness.